(untitled) (Research, Society and Development, 2020)
Objective: To reflect on the nurse’s performance and contribution, the light of ecosystem thinking, in the survival of the renal transplant recipient. Method: It is characterized as a theoretical-philosophical reflection about the contributions of nurses in the survival of the renal transplant recipient, the light of ecosystem thinking in analogy with authors who discuss health from an ecosystem perspective. Results and Discussion: The reflection was organized and discussed through three categories: Chronic kidney disease and kidney transplantation, from the ecosystem perspective; The work of nurses before and after transplantation; Contribution of the nurse’s performance in the survival of the renal transplant patient. It is inferred that the behavior can directly influence the survival of the user. Final considerations: It is observed the success of kidney transplantation depends on the guidance of the nurse to the user in relation to the best practices of prevention, maintenance care and, mainly, regarding the risks of infections, signs and symptoms of rejection of the transplanted organ. It is also noteworthy that by anchoring this study from an ecosystem perspective, it is up to the nurse’s performance beyond the high hospital environment that the literature indicates to us, but in the user’s home, where his post-transplant life and his/her survival really happen.